2020
DOI: 10.1101/2020.05.05.077156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent organization of aberrant MYB complex controls oncogenic gene expression in acute myeloid leukemia

Abstract: @KentsisResearch 2 HIGHLIGHTS • Cell-penetrant peptidomimetic inhibitor selectively blocks oncogenic MYB:CBP/P300 activity in diverse leukemias but not normal blood cells • MYB assembles aberrant transcription factor complexes in AML required for programming leukemic gene expression • CBP/P300 sequestration contributes to MYB-dependent leukemogenic gene expression and chromatin organization SUMMARYDysregulated gene expression is one of the most prevalent features in human cancers. Here, we show that most subty… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…While T/Myeloid MPALs showed higher levels of methylation in general, T-lymphoid ontogeny was reflected by hypomethylation of T-receptor signalling factor genes. Also in line with these concepts of global epigenetic dysregulation, recent intriguing data [97] have suggested that some cases of AML have epigenomic landscape changes reminiscent of the MYB regulatory complex reorganisation that is also found in T-ALL [98,99].…”
Section: Accepted Articlementioning
confidence: 75%
“…While T/Myeloid MPALs showed higher levels of methylation in general, T-lymphoid ontogeny was reflected by hypomethylation of T-receptor signalling factor genes. Also in line with these concepts of global epigenetic dysregulation, recent intriguing data [97] have suggested that some cases of AML have epigenomic landscape changes reminiscent of the MYB regulatory complex reorganisation that is also found in T-ALL [98,99].…”
Section: Accepted Articlementioning
confidence: 75%